2013
DOI: 10.1152/ajpgi.00317.2012
|View full text |Cite
|
Sign up to set email alerts
|

The hepatic bile acid transporters Ntcp and Mrp2 are downregulated in experimental necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is the most common gastrointestinal emergency of premature infants and is characterized by an extensive hemorrhagic inflammatory necrosis of the distal ileum and proximal colon. We have previously shown that, during the development of experimental NEC, the liver plays an important role in regulating inflammation in the ileum, and accumulation of ileal bile acids (BA) along with dysregulation of ileal BA transporters contributes to ileal damage. Given these findings, we speculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
4
15
0
Order By: Relevance
“…Conversely, hepatic downregulation of Slco1a4 (Oatp1a4) has been reported in fatty-liver disease, extrahepatic cancer, and experimental sepsis (Sharma et al, 2008;Fisher et al, 2009;Bodeman et al, 2013) as well as in the present study, but was not observed in necrotizing enterocolitis (NEC) or colitis caused by dextran sulfate sodium (DSS) treatment (Jahnel et al, 2009;Cherrington et al, 2013). C. rodentium infection also decreased Slco1a1 (Oatp1a1 or Oatp1) gene expression, which finding is consistent with reported downregulation after treatment with LPS or subcutaneous turpentine (Siewert et al, 2004;Bodeman et al, 2013).…”
Section: Drug Transporter Expression During C Rodentium Infection 599supporting
confidence: 92%
See 1 more Smart Citation
“…Conversely, hepatic downregulation of Slco1a4 (Oatp1a4) has been reported in fatty-liver disease, extrahepatic cancer, and experimental sepsis (Sharma et al, 2008;Fisher et al, 2009;Bodeman et al, 2013) as well as in the present study, but was not observed in necrotizing enterocolitis (NEC) or colitis caused by dextran sulfate sodium (DSS) treatment (Jahnel et al, 2009;Cherrington et al, 2013). C. rodentium infection also decreased Slco1a1 (Oatp1a1 or Oatp1) gene expression, which finding is consistent with reported downregulation after treatment with LPS or subcutaneous turpentine (Siewert et al, 2004;Bodeman et al, 2013).…”
Section: Drug Transporter Expression During C Rodentium Infection 599supporting
confidence: 92%
“…During live infection we observed a significant decrease in the mRNA expression of Abcc2 in C57BL/6J mice. Other inflammatory conditions have been reported to result in similar downregulation (Andrejko et al, 2008;Sharma et al, 2008;Cherrington et al, 2013). Multiple studies have indicated a role for IL-6 in the downregulation of Abcc2 (Siewert et al, 2004;Andrejko et al, 2008).…”
Section: Drug Transporter Expression During C Rodentium Infection 599mentioning
confidence: 87%
“…A slight upregulation of MDR1 (ABCB1), as observed previously (Poller et al, 2010), was not significant. Transcriptional downregulation of the hepatic bile acid transporter NTCP (SLC10A1) is in agreement with a former study (Cherrington et al, 2013). Somewhat more extended effects of IL-1b and TNF-a were also observed for HNF4A, PPARA, and POR.…”
supporting
confidence: 91%
“…Interestingly, the models that used MCD feeding share the most similarity to drug transporter expression in human NASH. It is well known that MCD feeding causes significant induction of oxidative stress as well as the release of proinflammatory cytokines, both of which are mediators of drug transporter gene regulation (Leclercq et al, 2000;Chowdhry et al, 2010;Cherrington et al, 2013;Ikemura et al, 2013). Additionally, hepatic oxidative stress is increased in humans with NASH leading to aberrations in oxidative stress-mediated gene regulation (Hardwick et al, 2010).…”
Section: Discussionmentioning
confidence: 99%